-
For the circuit shown in the given figure, if input impedance Z1 at port 1 is given by
Z1 = K1 (s + 2) s + 5
then input impedance Z2 at port 2 will be
-
-
K2(s + 3) s + 5
-
K2(s + 2) s + 3
-
K2 s s + 5
-
K2 s s + 2
-
Correct Option: C
Z1 = K1 | ||
s + 5 |
∴ Z1 = R1 | ||
R1 + R2 + Ls |
= | R1L | ![]() | ![]() | ![]() | ![]() | |
L + (s) | ||||||
L | ![]() | ![]() | ![]() | ![]() | ||
L + (s) |
= | R1 | ![]() | ![]() | ![]() | ![]() | |
L + (s) | ||||||
![]() | ![]() | ![]() | ![]() | |||
L + (s) |
∴ R1 = K1
= 2 , | = 5 | |||
L | L |
Again , R2 = | K1 , L = | |||
3 | 3 |
∴ Z2 = | ||
Ls + R2Cs |
= | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | |||
3s | 3K1 | ||||||||
![]() | ![]() | sK1 + | ![]() | ![]() | ![]() | ![]() | |||
3 | 3K1 |
= | s | ![]() | ![]() | |
3K1 | = | |||
(s + 5) | (s + 5) |
∴ K2 = | K1 | |
3 |